2010
DOI: 10.1016/j.bbabio.2010.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Cold tolerance of UCP1-ablated mice: A skeletal muscle mitochondria switch toward lipid oxidation with marked UCP3 up-regulation not associated with increased basal, fatty acid- or ROS-induced uncoupling or enhanced GDP effects

Abstract: Mice lacking the thermogenic mitochondrial membrane protein UCP1 (uncoupling protein 1)--and thus all heat production from brown adipose tissue--can still adapt to a cold environment (4 degrees C) if successively transferred to the cold. The mechanism behind this adaptation has not been clarified. To examine possible adaptive processes in the skeletal muscle, we isolated mitochondria from the hind limb muscles of cold-acclimated wild-type and UCP1(-/-) mice and examined their bioenergetic chracteristics. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 87 publications
7
83
1
Order By: Relevance
“…2). Since body weight remained nearly identical in the two genotypes, it appears that the ␣ 1 -AMPK Ϫ/Ϫ mice 1) preferentially used nonepididymal fat or 2) catabolized nonadipose tissue sources such as skeletal muscles to generate the heat needed to maintain body temperature (28). Our data indicate that failure of ␣ 1 -AMPK Ϫ/Ϫ mice to use epididymal fat was not due to lower-than-normal levels of P-HSL.…”
Section: R477 Responses To Cold and Thermogenesis Of Ampk ϫ/ϫ Micementioning
confidence: 63%
See 1 more Smart Citation
“…2). Since body weight remained nearly identical in the two genotypes, it appears that the ␣ 1 -AMPK Ϫ/Ϫ mice 1) preferentially used nonepididymal fat or 2) catabolized nonadipose tissue sources such as skeletal muscles to generate the heat needed to maintain body temperature (28). Our data indicate that failure of ␣ 1 -AMPK Ϫ/Ϫ mice to use epididymal fat was not due to lower-than-normal levels of P-HSL.…”
Section: R477 Responses To Cold and Thermogenesis Of Ampk ϫ/ϫ Micementioning
confidence: 63%
“…For example, ␣ 2 -AMPK activity may be sufficient to accommodate the increased metabolic demands of chronic cold exposure. Interestingly, chronic cold exposure caused a further upregulation of ␣ 2 -AMPK beyond that caused by loss of ␣ 1 -AMPK in WAT and skeletal muscle, both of which are major contributors to body temperature maintenance during cold exposure (11,28).…”
Section: R477 Responses To Cold and Thermogenesis Of Ampk ϫ/ϫ Micementioning
confidence: 99%
“…Mitochondrial isolation, respiration and ROS measurements In a second set of mice (n07 per group) on the same diet and intervention regimen as that described above, skeletal muscle mitochondria were isolated and respiration was measured as previously described [25,26]. Respiration rates in isolated mitochondria (0.1 mg/ml) were determined at 37°C by polarographic oxygen sensors in a two-chamber Oxygraph (Oroboros Instruments, Innsbruck, Austria) using pyruvate (5 mmol/l) plus malate (3 mmol/l), or palmitoyl-coenzyme A (CoA) (50 μmol/l) plus carnitine (2 mmol/l) as substrates.…”
Section: Methodsmentioning
confidence: 99%
“…For instance Wijers et al (2008) have demonstrated increased state 4 oxygen consumption in skeletal muscle mitochondria isolated from cold-acclimated humans. However, a recent study using cold acclimated wild-type and UCP1 knock-out mice states that "UCP3 is not innately uncoupling, that it cannot be induced to act as an uncoupler by either fatty acids or by endogenous reactive oxygen species, and that effects of GDP on respiration are not mediated by UCP3 study" (Shabalina et al, 2010). Interestingly, Sun et al (2003) have demonstrated that increased UCP3 protein levels in rat skeletal muscle following lipopolysaccharide/dexamethosone injection, possibly indicating a role for UCP3 involvement in thermogenesis in sepsis.…”
mentioning
confidence: 99%